Beneficial role of Sn in rapid rust stabilization of weathering steel in marine environments - Yang, Liu; Cheng, Xuequn; Li, Xiaogang (International journal of minerals, metallurgy and materials, 2025)
Weathering steel exhibits excellent corrosion resistance and is widely used in bridges, towers, railways, highways, and other engineering projects that are exposed to the atmosphere for long periods of time. However, before the formation of stable rust layers, weathering steel is prone to liquid rust sagging and spattering, leading to environmental pollution and city appearance concerns. These factors limit the application and development of weathering steel. In this study, a rapid and environmentally friendly method was developed by introducing alloying elements, specifically investigating the role of Sn in the rapid stabilization of rust layers in marine atmospheric environments. The rust layer formed on weathering low-alloy steel exposed to prolonged outdoor conditions and laboratory immersion experiments was explored using electron probe micro-analyzer (EPMA), micro-Raman, X-ray photoelectron spectroscopy (XPS), and electrochemical measurements. Results showed an optimal synergistic effect between Sn and Cr, which facilitated the accelerated densification of the rust layer. This beneficial effect enhanced the capability of the rust layer to resist Cl − erosion and improved the protection performance of the rust layer.